Present-day testing of a paleoecological pattern : is there really a latitudinal difference in leaf-feeding insect-damage diversity? - Adams, Jonathan M.; Brusa, Anthony; Soyeong, Ahn; Nuruddin, Ahmad Ainuddin (Elsevier, 2010)
The fossil record suggests greater diversity of insect leaf feeding during warm climate intervals. Much published work in the paleobotanical literature has been based on the presumed validity of this pattern. However, the existence of this pattern in nature has never been tested from the present-day world. Here we ask, is it true that on average, in warmer climates, a leaf is being eaten in more ways?